PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN WAROENG SPESIAL SAMBAL (SS) DI YOGYAKARTA - Laila, Novi Nur; Zuraida, Lukia (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This research is based on the working environment conditions in the Special Sambal (SS) waroeng which has a narrow work space, especially in the kitchen, and the workload requires working quickly but still must pay attention to customer satisfaction at the Special Sambal (SS) waroeng. The aim of this research is to explain the influence of work motivation, work environment and workload on employee performance and to show the variables that most influence the performance of employees at the Special Sambal (SS) waroeng in Yogyakata. This research uses quantitative methods. The sample in this study were employees of the Special Sambal (SS) waroeng in Yogyakata with a total of 100 respondents. The analysis method uses multiple linear regression analysis with the help of the SPSS version 22 program. The results of the research show that work motivation has no effect on employee performance, work environment and workload have an effect on employee performance, and simultaneously work motivation, work environment and workload have an effect on employee performance at Waroeng Spesial Sambal (SS) in Yogyakarta. The research results show that the most dominant variable that influences employee performance is workload.